Circulation, writing, and rhetoric - Gries, Laurie E.; Brooke, Collin Gifford (Logan : Utah State University Press, 2018)
"It has been understood that writers quote, imitate, forward, borrow, dispute, engage with, and transform texts written by others. Contributors identify circulation as a threshold concept of Western literacy theory and explore five key themes concerning circulation: public rhetorics, feminism, new materialism, theories of delivery, and technologies"--Provided by publisher.
13. Circulation Analytics: Software Development and Social Network Data / Aaron Beveridge14. Open Access(ibility?) / Jay Dolmage; Responses; 15. Circulation Exhaustion / Jenny Rice; 16. Archival Problems, Circulation Solutions / Jessica Enoch; 17. Circulation-Signification-Ontology / Thomas Rickert; 18. A Diagrammatics of Persuasion / Byron Hawk; 19. The Spaces Between / Sidney I. Dobrin; Afterword: The Futurity of Circulation Studies / Laurie E. Gries; About the Authors; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 2, 2018).
JSTOR
Keywords: Rhetoric -- Social aspects; Communication in learning and scholarship; Rhétorique -- Aspect social; Communication savante; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; Communication in learning and scholarship; Rhetoric -- Social aspects